The Impact of Transformational Leadership on Improving Social Science Teaching Quality - Imam Sibaweh; Aan Komariah; Diding Nurdin; Nur Aedi (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
This research investigates the effect of transformational leadership on enhancing the quality of Social Science teachers. The leadership model is explored through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Teacher quality improvement is assessed using Juran’s trilogy framework, which consists of quality planning, quality control, and quality improvement. The study was conducted at Yayasan Al Kautsar Cirebon, involving three school principals and six teachers representing MI, MTs, and Ulya levels. Several research gaps were identified: (1) the influence of each leadership dimension varies depending on the school context; (2) there is a need for broader and more comprehensive indicators of teacher quality; and (3) the relatively small sample size limits the generalizability of the findings. A quantitative approach with a survey design was applied, and data were processed through descriptive statistics, Pearson correlation to examine variable relationships, and linear regression to determine the most dominant leadership factor in improving teacher quality. The findings demonstrate that transformational leadership significantly and positively contributes to teacher quality improvement, with intellectual stimulation and individualized consideration emerging as the strongest predictors. Based on these results, the study recommends that principals emphasize these two aspects to strengthen instructional quality through diverse teaching strategies.Keywords: Leadership Transformational, Quality Improvement, Social Sains Teachers.